A mindful yoga intervention for children with severe asthma: A pilot study. (August 2020) - Lack, Sharon; Schechter, Michael S.; Everhart, Robin S.; Thacker II, Leroy R.; Swift-Scanlan, Theresa; Kinser, Patricia A.
Abstract: Introduction: Children with severe asthma may benefit from non-pharmacological approaches to symptom management, yet little is known regarding the impact of mind-body approaches such as mindful yoga in this population. This pilot study examined the tolerability, feasibility, acceptability and immediate effects of a mindful yoga intervention in children with severe asthma. Method: Fifteen children ages 7–11 with severe asthma participated in a single mindful yoga session, followed by semi-structured interviews with the child and caregiver. Vital signs and pulmonary function tests were collected pre- and post-intervention. Results: All children reported positive experiences and caregivers were generally supportive of their participation. One child experienced self-limited bronchoconstriction with asthma symptoms. There was no significant change in lung function or vital signs after the mindful yoga session. Discussion: Our results warrant additional larger studies to evaluate the safety and benefits of mindful yoga in children with severe asthma. Highlights: Children with severe asthma participated in one session of mindful yoga. Lung function and vitals were obtained pre/post the session. The children discussed their thoughts and feelings about the mindful yoga. They did not have any significant asthma symptoms and they enjoyed it. Future research with additional sessions iswarranted with this population.